Rotary versus manual instrumentation for root canal preparation in primary teeth: A systematic review and meta-analysis of clinical trials - Reyhaneh Faghihian; Kiana Amini; Dana Tahririan (Wolters Kluwer Medknow Publications, 2022)
Objectives: The aim of this systematic review was to assess the scientific evidence on the effect of rotary versus manual instrumentation for root canal preparation in primary teeth. Materials and Methods: Search terms were selected based on Medical Subject Headings (MeSH) and non-MeSH terms. Electronic database search of English published literature was performed in March 2020 within the following databases: Scopus, Cochrane, PubMed, and Embase. The risk of bias of selected studies was assessed by means of Cochrane collaboration tool. The heterogeneity level among the included studies was measured by I2 index. For statistical analysis of instrumentation time, standard mean difference (SMD) of continuous data was analyzed with 95% confidence intervals (95% CIs) using the fixed-effects model. A random-effects model was used for analysis of odds ratio (OR) to assess the probability of optimal fill, underfill, and overfill obturations. Forest plots were applied to show the results and to estimate the effectiveness of rotary instrumentation. Results: Seven articles were selected for this review. The SMD in rotary techniques was 1.79 min less than manual techniques (95% CI: −2.56-−1.03 min) and had a significant P = 0.001. The OR of optimum quality was calculated to be 3.53 (95% CI: 1.79-6.97) in the rotary technique at P = 0.254. Conclusions: Within the limitations of this review, it can be asserted that rotary files decrease the instrumentation time and increase the rates of optimally filled canals in primary teeth. However, these files do not decrease the risk of underfilling and overfilling compared to manual files.